Neutron Stars Today - Horvath, Jorge Ernesto (2021)
Neutron stars today are not what they used to be. Several myths about their origins and properties have been refuted by the availability of new observations. We present the status of the present knowledge about their birth events and properties, focusing on their mass distributions, which is now known to be at least bimodal. We argue that “spider” relativistic binaries may produce the heaviest neutron stars and possibly the lightest black holes in Nature. The (delicate) issue of the maximum mass will be discussed with reference to i) direct determinations; ii) statistical tools and iii) analysis of gravitational waves events. Overall, we shall show that a new perspective of these objects is emerging.